The accuracy of online-based prayer times applications - encep abdul rojak; Ilham Mujahid; Muhammad Yunus (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2021)
There are various types of prayer times that Muslims refer to on a daily basis. Specifically, there are offline and online prayer times as well as traditional and modern prayer times. Online prayer times that can be accessed from a mobile phone in forms such as android-based applications, online websites, and Google applications. The purpose of this study is to investigate the accuracy of online-based prayer times applications and seek for the possible consistency across these applications. This study employs a qualitative approach and a descriptive data analysis. The data collection is conducted through observations, literature study, and in-depth interviews. This study indicates different degree of deviations among online-based prayer times applications, in which Google applications show the most deviation among the others. This study suggests that Muslims refer to online applications recommended by the Ministry of Religious Affairs of Indonesia.